Evidence for the presence of muscarinic M-2 and M-4 receptors in guinea-pig gallbladder smooth muscle - KARAALP, ATİLA; CABADAK, HÜLYA; ORUN, OYA (WILEY, 1998)
1 The affinities of 10 selective muscarinic receptor antagonists against [H-3]-quinuclidinyl benzilate (QNB) binding were determined to characterize the muscarinic receptors present in guinea-pig gallbladder smooth muscle. The highest correlation was obtained for the comparison between the pK(i) values for the gallbladder smooth muscle and M-2 sites. Pirenzepine revealed two binding sites with affinities indicating the presence of muscarinic M-2 receptors in abundance and a minor population of an additional site(s). 2 Carbachol produced gallbladder contractions, stimulated phosphoinositide (PI) hydrolysis and inhibited cAMP formation concentration-dependently with pD(2) values of 6.12 +/- 0.11, 5.18 +/- 0.33 and 7.19 +/- 0.15, respectively. 3 Pirenzepine, 4-DAMP, HHSiD, pF-HHSiD, AF-DX 116, methoctramine, AQ-RA 741, guanylpirenzepine and AF-DX 384 showed competitive antagonism against carbachol-induced gallbladder contractions. There was no correlation between the pA(2) values for the gallbladder and pK(i) values for the M-2 sites, whereas significant correlations were found for the M-1, M-3 and M-4 sites, the best correlation being between the pA(2) values for the gallbladder and M-4 subtypes. 4 Finally, the presence of both m(2) and m(4) receptor proteins were demonstrated by Western blot analysis. It is concluded that guinea-pig gallbladder smooth muscle has both muscarinic M-2 and M-4 receptors, which are coupled to adenylate cyclase inhibition and PI hydrolysis. 5 Although it seems likely that Mt receptors do not play a primary role in carbachol-induced guinea-pig gallbladder contraction, the characterization of the muscarinic subtypes which mediate these contractile responses needs further evidence.
Keywords: SIGNAL-TRANSDUCTION PATHWAYS; SUBTYPE-SPECIFIC ANTIBODIES; ADENYLATE-CYCLASE; BINDING-PROPERTIES; PHOSPHOINOSITIDE TURNOVER; ACETYLCHOLINE-RECEPTORS; ANTAGONIST; INHIBITION; M2; HETEROGENEITY